Binaural processing and phonological awareness in Australian Indigenous children from the Northern Territory: A community based study. (January 2020) - Sharma, Mridula; Wigglesworth, Gillian; Savage, Gemma; Demuth, Katherine
Abstract: Objective: Research has found that otitis media (OM) is highly prevalent in Australian Indigenous children, and repeated bouts of OM is often associated with minimal-to-moderate hearing loss. However, what is not yet clear is the extent to which OM with hearing loss impacts auditory signal processing specifically, but also binaural listening, listening in noise, and the potential impact on phonological awareness (PA) – an important, emergent literacy skill. The goal of this study was to determine whether auditory abilities, especially binaural processing, were associated with PA in children from populations with a high incidence of OM, living in a remote Australian Indigenous community in the Northern Territory (NT). Methods: Forty-seven 5-12-year-olds from a bilingual school participated in the study. All were tested to determine hearing sensitivity (pure tone audiometry and tympanometry), with PA measured on a test specifically developed in the first language of the children. OM often results in a hearing loss that can affect binaural processing: the Dichotic Digit difference Test (DDdT) was used to evaluate the children's dichotic listening and the Listening in Spatialized Noise-sentences test (LiSN-S) was used to evaluate their abilities to listen to speech-in-noise. Results: Seventeen (36%) and 16 (34%) had compromised middle ear compliance (combined Type-B and –C) in the right and left ear respectively. Six children demonstrated a bilateral mild hearing loss, and another five children demonstrated a unilateral mild hearing loss. Thirty-one children were able to complete the DDdT listening task, whereas only 24 completed the speech in noise task (LiSN-S). Forty-four children (94%) were able to complete the letter identification subtask, comprising part of the PA task. The findings revealed that age was significantly correlated with all tasks such that the older children performed better across the board. Once hearing thresholds were controlled for, PA also correlated significantly with both binaural processing tasks of dichotic listening (r = 0.59, p  < 0.001) and listening to speech in noise (r = −0.56, p  = 0.005); indicating a potential association between early, emergent literacy and listening skills. Conclusions: The significant correlations between phonological awareness and dichotic listening as well as phonological awareness with listening to speech-in-noise skills suggests auditory processing, rather than hearing thresholds per se, are associated to phonological awareness abilities of this cohort of children. This suggests that the ability to process the auditory signal is critical.